1998
DOI: 10.1074/jbc.273.25.15313
|View full text |Cite
|
Sign up to set email alerts
|

Agmatine Suppresses Proliferation by Frameshift Induction of Antizyme and Attenuation of Cellular Polyamine Levels

Abstract: Polyamines are required for entry and progression of the cell cycle. As such, augmentation of polyamine levels is essential for cellular transformation. Polyamines are autoregulated through induction of antizyme, which represses both the rate-limiting polyamine biosynthetic enzyme ornithine decarboxylase and cellular polyamine transport. In the present study we demonstrate that agmatine, a metabolite of arginine via arginine decarboxylase (an arginine pathway distinct from that of the classical polyamines), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
113
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 20 publications
10
113
1
1
Order By: Relevance
“…Agmatine binds to α # -adrenergic and imidazoline receptors [271], suggesting a role in cell signalling. Agmatine can also inhibit ODC activity by inducing synthesis of antizyme, thus suppressing cell proliferation by reducing cellular polyamine concentrations [278]. Finally, agmatine is a weak competitive inhibitor of the NOS isoenzymes [279], suggesting that it may be an endogenous regulator of NO synthesis if local agmatine concentrations are sufficiently high.…”
Section: Arginine Decarboxylasementioning
confidence: 99%
“…Agmatine binds to α # -adrenergic and imidazoline receptors [271], suggesting a role in cell signalling. Agmatine can also inhibit ODC activity by inducing synthesis of antizyme, thus suppressing cell proliferation by reducing cellular polyamine concentrations [278]. Finally, agmatine is a weak competitive inhibitor of the NOS isoenzymes [279], suggesting that it may be an endogenous regulator of NO synthesis if local agmatine concentrations are sufficiently high.…”
Section: Arginine Decarboxylasementioning
confidence: 99%
“…It has been shown that treatment of cells with the rare polyamine, agmatine, suppresses proliferation by frame-shift induction of Az and attenuation of cellular polyamine levels (Satriano et al, 1998). Moreover, HTC (rat liver hepatoma derived from Morris hepatoma) cells treated with agmatine showed a progressive accumulation of cells in G 2 /M phase of the cell cycle with no evident signs of apoptosis or necrosis (Gardini et al, 2003).…”
Section: Antizyme1-dependent Aurora-a Degradation Sk Lim and G Gopalanmentioning
confidence: 99%
“…Increased polyamine uptake also accompanies growth as polyamine transport is stimulated by many of the same factors that induce ODC. Polyamines are autoregulated through induction of the inhibitory protein, namely (ODC-) antizyme, which inhibits both ODC for polyamine synthesis and cellular polyamine transport (Satriano et al 1998). In previous studies we have shown that agmatine administration induces antizyme expression, depletes intracellular polyamine levels, and suppresses cellular proliferation in a transformed murine proximal tubule cell line (Satriano et al 1998).…”
mentioning
confidence: 99%
“…Polyamines are autoregulated through induction of the inhibitory protein, namely (ODC-) antizyme, which inhibits both ODC for polyamine synthesis and cellular polyamine transport (Satriano et al 1998). In previous studies we have shown that agmatine administration induces antizyme expression, depletes intracellular polyamine levels, and suppresses cellular proliferation in a transformed murine proximal tubule cell line (Satriano et al 1998). Furthermore, agmatine utilizes, and is dependent upon, the polyamine transporter for cellular uptake (Satriano et al 2001b).…”
mentioning
confidence: 99%
See 1 more Smart Citation